CONVERSATIONAL IMPLICATURE APPLIED IN YOUNG LEARNER’S RUMPELSTILTSKIN - Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2018)
English children story book is written aimed at boosting their English reader’ proficiency as well as their performance in reading. This study is conducted to analyze the conversational implicature recognized in children story book. The object of the study is the story entitled Rumpelstiltskin published by Indian publisher. This study is conducted aimed at finding kinds of conversational implicature recognized in the Young Learner’s story book. Children story book written in English is published to help them learn English. English in Indonesia is as the first foreign language learnt while other countries within Asian continent have English as their second language. TEFL in Indonesia needs more time to make Indonesian students accustomed to use English in their daily conversation. Book is written in many genres and one of it is narrative. Narrative text type is commonly found in the story therefore the author used their imagination in order to help the readers build their own imagination. Building imagination is part of the activity to help children to be creative. The children are still on their growing period therefore they need many stimulus to help them gain more information stored in their brain. India is one of Asian’s country which English as their second language therefore Indian people speak English better than Indonesian. Though Indian as a country is similar to Indonesia in terms of population but they are more productive in using English. Indonesian people should learn from Indian people in using English since English language is used formally at public places including school. Indian authors are also more productive in writing and one of the writing that I analyze in this study is the children’s story belongs to Young Learner’s series. I chose Indian book because I believe that children’s reader will learn and understand English language easily. Keywords: reading, English story book, conversational implicature